Modifiable child and caregiver factors that influence community participation among children with Down syndrome. Issue 4 (13th February 2022) - Shields, Nora; Epstein, Amy; Jacoby, Peter; Kim, Rachel; Leonard, Helen; Reddihough, Dinah; Whitehouse, Andrew; Murphy, Nada; Downs, Jenny
Abstract: Purpose: To investigate modifiable child and caregiver factors influencing community participation among children with Down syndrome. Methods: Cross-sectional data from a study investigating quality of life of children with intellectual disability were analysed. Participants were caregivers of 89 children with Down syndrome (54 females; 83 school attenders) (mean age 11 y 1 mo; SD 4 y 1 mo). Components of participation ( attendance, involvement ) were measured using the Participation and Environment Measure for Children and Youth, community module. Caregiver factors were time, mood, transport, and disability funding. Child factors were sleep, behaviour, communication, and health. Multivariate linear regression analyses examined if (i) caregiver factors were associated with attendance and (ii) child factors were associated with involvement. Results: Increased caregiver time availability was associated with higher frequency of attendance. Higher frequency of attendance was associated with greater child involvement, and having a sleep breathing disorder and less verbal communication ability was associated with less child involvement. These factors combined explained 21% of the variance. Conclusions: Children with Down syndrome who participated in the community more frequently enjoyed greater involvement. Supporting participation of children with poorer verbal communication and/or sleep breathing disorders could further the participation of children with Down syndrome. Implications for rehabilitation: Children with Down syndrome who more frequently attended opportunities for participation were more likely to be involved in those experiences. Healthcare providers and educators could foster involvement in participation opportunities of children with poorer verbal ability by supporting the development of prerequisite communication strategies. Rehabilitation programs and policies pertaining to accessibility of community activities need to align with modifiable determinants of participation in children, including availability of caregivers' time.